2017
DOI: 10.1128/mcb.00461-16
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat Diet Promotes Mammary Gland Myofibroblast Differentiation through MicroRNA 140 Downregulation

Abstract: Human breast adipose tissue is a heterogeneous cell population consisting of mature white adipocytes, multipotent mesenchymal stem cells, committed progenitor cells, fibroblasts, endothelial cells, and immune cells. Dependent on external stimulation, adipose-derived stem cells differentiate along diverse lineages into adipocytes, chondrocytes, osteoblasts, fibroblasts, and myofibroblasts. It is currently not fully understood how a high-fat diet reprograms adipose-derived stem cells into myofibroblasts. In our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…Lactation imposes a significant energy demand by the mammary gland. Additionally, HFD feeding has been reported to cause significant effects on mammary gland adipose tissue (39) and myofibroblast differentiation (64). At the computational level, three genes (DDR1, Atp2b2, and Csf1) with a reported role in mammary gland ductal development were confirmed to exhibit significant differential isoform expression between HFD and LFD dams.…”
Section: High-fat Diet Impacts Peak Lactation Mammary Glandmentioning
confidence: 92%
See 1 more Smart Citation
“…Lactation imposes a significant energy demand by the mammary gland. Additionally, HFD feeding has been reported to cause significant effects on mammary gland adipose tissue (39) and myofibroblast differentiation (64). At the computational level, three genes (DDR1, Atp2b2, and Csf1) with a reported role in mammary gland ductal development were confirmed to exhibit significant differential isoform expression between HFD and LFD dams.…”
Section: High-fat Diet Impacts Peak Lactation Mammary Glandmentioning
confidence: 92%
“…Additionally, breastmilk composition changes due to nutritional modification have been proven to have long-term effects on offspring, further highlighting the importance of breastmilk in early life (21). Some studies have shown transcriptomic changes in milk or mammary gland in animal models fed an HFD (20,64). A recent study found that mice fed an HFD before and during lactation have significantly altered microRNA expression lev-els as well as whole transcriptome changes in milk (14).…”
Section: Introductionmentioning
confidence: 99%
“…To further examine extracellular matrix deposition, we performed IHC staining for fibronectin, a primary component of the basement membrane. We recently identified fibronectin as a direct target of miR‐140, and found that chow‐fed miR‐140 knockout mice had upregulated expression of fibronectin compared to WT . As demonstrated in Figure A, there was a small, insignificant increase in central vein fibronectin expression in WTHFD mice compared to WTLFD.…”
Section: Resultsmentioning
confidence: 93%
“…Through utilization of a diet‐induced obesity mouse model, we found that obesity downregulates miR‐140 expression in the stromal mammary gland through TGFβ induced SMAD3 signaling. Moreover, we demonstrated that loss of miR‐140 results in a feedback loop that drives mammary myofibroblast differentiation, promoting the development of a fibrotic mammary microenvironment . As we demonstrated that high‐fat diet resulted in miR‐140 downregulation, we wanted to determine whether miR‐140 loss is sufficient to serve as one of the necessary “hits” in the development of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…During apoptotic stimuli, miR-140 is upregulated, contributing to the suppression of Mfn1 expression during apoptosis (63). Interestingly, miR-484 and miR-140 have been reported to be reduced in obesity (81,116).…”
Section: Fission-fusionmentioning
confidence: 99%